GAMBARAN KARAKTERISTIK PENDERITA FILARIASIS DI DESA SANGGU KABUPATEN BARITO SELATAN KALIMANTAN TENGAH - Vipi Nurpila (Jurnal Kesehatan Masyarakat (Undip), 2016)
Barito Selatan is one of the endemic areas of filariasis with Mf rate of 1.34% in 2004. MDA filariasis has been carried out in 2005-2013 gradually. Transmission assessment survey in 2014 obtained Mf rate of 1.7% with most cases in the village Sanggu. As a result, South Barito must add MDA Filariasis 2 years. MDA filariasis 2015 have done. The purpose of this study was to evaluate the filariasis mass treatment in the village Sanggu South Barito regency in Central Kalimantan.This research is a descriptive with cross sectional design. The sample was part of filariasis MDA target in 2015 aged > 2 years in the village of Sanggu. The sampling technique using a simple random sampling. Determination of sample size on a calculation done through the use estimed propotion formula as many as 102 people. With the inclusion criteria are willing to become respondent and age < 15 years accompanied by a parent. While the criteria for inclusion of respondents move home,pregnant and children aged < 5 years of marasmus.The results showed that the rate Mf Sanggu Village at 2.9% with type B. malayi microfilariae.